Theories of Personal Income Distribution: A Survey - Sahota, Gian S. (Journal of Economic Literature, 2007)
I wish to express my appreciation to thefollowingfor their comments and suggestions either in their capacity as the referees of this journal or otherwise: Anthony Atkinson, Zvi Griliches, Martin Bronfenbrenner, Rudolph Blitz, James Buchanan, Milton Friedman, James Meade, Jacob Mincer, Franco Modigliani, Naomi Perlman, John Rawls, Paul Schultz, Gerald Sazama, Joseph Stiglitz, Paul Taubman, Lester Thurow, and Charles Wilson. None of them, however, bears any responsibility for my errors and my appraisal of different theories. I dedicate this paper to the memory of Harry G. Johnson, my teacher, who died at the early age of 53 on 9 May 1977, a few months after we had exchanged correspondence on this survey and had plans for further discussion, especially on the development of his ideas about cultural inheritance. Alas, that was the end.